Thyrotropin Stimulates Differentiation Not Proliferation of Normal Human Thyrocytes in Culture - Morgan, Sarah J.; Neumann, Susanne; Marcus-Samuels, Bernice; Gershengorn, Marvin C. (Frontiers in Endocrinology, 2016)
Although TSH has been suggested to be a proliferative agent for thyrocytes, the effect of TSH on human thyroid cells remains controversial. In particular, most of the reported studies relied primarily on changes in DNA synthesis but have not included measurement of the number of cells. We argue that only a direct count of cell number, demonstrating classical exponential expansion, serves as a valid measurement of proliferation. Thus, although some data support TSH as a proliferative agent, most do not provide conclusive evidence. To generate conclusive evidence with regard to a proliferative effect of TSH in human thyrocytes, we performed various experiments using primary cultures of human thyrocytes. In contrast to previous reports, TSH [±insulin-like growth factor 1 (IGF-1)] did not induce proliferation of thyrocytes under a variety of different conditions. However, TSH/IGF-1 cotreatment did upregulate thyroid-specific gene expression including thyroglobulin (TG) and TSHR in a manner consistent with cellular differentiation. Evidence for a proliferative effect of TSH has been used to inform the American Thyroid Association’s guidelines for the management of thyroid cancer patients, which include TSH suppression. While these recommendations are admittedly based on low- to moderate-quality evidence, TSH suppression is still widely used. We present data that question the consensus view that TSH promotes proliferation of human thyrocytes (upon which the American Thyroid Association’s guidelines are based) and suggest that additional studies, including randomized controlled trials, are warranted to address this important clinical question.